1990
DOI: 10.1203/00006450-199004000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific Disposition of Group B Streptococci in Piglets: Evidence for a Direct Interaction with Target Cells in the Pulmonary Circulation

Abstract: ABSTRACT. Despite the serious pulmonary manifestaintact animal could be initiated by a direct interaction tions of early onset group B streptococcal (GBS) sepsis, it between GBS and resident lung cells without obligatory is not known whether the organism distributes into lung participation by other organ systems. (Pediatr Res 27: tissue and whether adverse pulmonary hemodynamic ab-344-348,1990) normalities relate to an interaction between the organism and target cells in the pulmonary vascular bed. AccordAbbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1993
1993
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…We and others have proposed that bacteriaor particulate-induced activation of an oxygen radical-dependent microbicidal mechanism residing within PIM is a key stimulus for mediator release and acute pulmonary hypertension (7). In support of this contention, we have shown that a substantial proportion of GBS deposits in the lungs of intact infant piglets, where approximately half of the organisms are nonviable within a 60-min period (7,8). Interestingly, the severity of the pulmonary hypertensive response was inversely related to the percentage of bacteria remaining alive in the lung.…”
supporting
confidence: 62%
See 4 more Smart Citations
“…We and others have proposed that bacteriaor particulate-induced activation of an oxygen radical-dependent microbicidal mechanism residing within PIM is a key stimulus for mediator release and acute pulmonary hypertension (7). In support of this contention, we have shown that a substantial proportion of GBS deposits in the lungs of intact infant piglets, where approximately half of the organisms are nonviable within a 60-min period (7,8). Interestingly, the severity of the pulmonary hypertensive response was inversely related to the percentage of bacteria remaining alive in the lung.…”
supporting
confidence: 62%
“…At equivalent Pdo, GBS evoked greater increases in lung weight than U44069. DISCUSSION GBS deposits in the lungs of intact, newborn piglets, where the bacteria are apparently killed in part by an oxygen radicaldependent mechanism (7,8). In this complicated preparation, it is not possible to determine whether lung cells mount a pathophysiologically relevant microbicidal response to intravascular bacteria or whether cell populations remote from the lungs and/ or circulating blood cells kill bacteria that then localize in the lung.…”
Section: Gbs Uptake and Viability In Isolatedpiglet Lungsmentioning
confidence: 99%
See 3 more Smart Citations